The Performance Degradation of Red, Green, and Blue Micro-LEDs Under High-Temperature Electrical Stress - Changdong Tong; Yu Liu; Quan Deng; Li Pan; Guolong Chen; Yijun Lu; Tingzhu Wu; Zhong Chen; Weijie Guo (Crystals, 2025)
In this work, the degradation in luminous characteristics of red, green, and blue (RGB) micro-LEDs (10 µm × 10 µm) under electrical stress at 360 K has been investigated. After 280 h of aging, the AlGaInP-based red micro-LEDs exhibit a 31.7% reduction in maximum external quantum efficiency, which is significantly greater than the reductions observed in InGaN-based green and blue micro-LEDs. Specifically, the peak wavelength redshift by 0.6 nm, and blueshift 1.0 nm, and 0.5 nm for RGB micro-LEDs, respectively. The color purity of green and blue micro-LEDs decreases by 3.6% and 0.7%, respectively, resulting in a 7% reduction in color gamut.